Health Promotion and Diabetic Foot Exercises: Improving Foot Sensitivity in Elderly Diabetic Patients - Priyanto, Sigit; Kristiyanto, Agus; ., Kusnandar; Lestari, Anik (Journal of Posthumanism, 2025)
Diabetes mellitus increases the risk of impaired blood circulation and foot sensitivity in peripheral areas, which can lead to diabetic ulcers. This can be prevented by controlling glucose levels through education, physical activities, and diet management. One of the efforts to improve foot sensitivity is through diabetic foot exercises. Education through health promotion is essential to evaluate the compliance of diabetes mellitus patients in performing diabetic foot exercises. Therefore, this study aims to determine the effect of health promotion on compliance with diabetic foot exercises in increasing foot sensitivity in people with diabetes mellitus in Magelang Regency.This study used a quasi-experimental design with pre and post-tests and a control group. The sampling technique used proportional random sampling with a total of 124 respondents, consisting of 62 respondents in the intervention group and 62 in the control group. Foot exercises were conducted for 12 weeks, and foot sensitivity was measured before and after the intervention. The results showed a difference in compliance with diabetic foot exercises and foot sensitivity before and after health promotion in both the intervention and control groups, with a p-value of 0.000. In the intervention group, foot sensitivity increased with an average score of 1.661 before the intervention and 2.161 after the intervention. No significant increase was observed in the control group (p = 0.083). Additionally, there was a significant difference in HbA1c levels between the intervention and control groups after the intervention (p = 0.000). In conclusion, health promotion significantly influences compliance with diabetic foot exercises and foot sensitivity in patients with diabetes mellitus. It is recommended to implement an appropriate health promotion model for diabetes mellitus management.